Abortion-related complications in Brazil: results from the World Health Organization Multi-country Survey on Abortion (MCS-A) - Nelio Neves Veiga Junior; Luiz Francisco Cintra Baccaro; Adriana Mendonça da Silva Alexandrino; Alexandre Volta Andrade do Nascimento; Camila Tereza Camilo Clerot; Cintya Andreia do Nascimento Santos; Claudia Lucrécia de Matos Silva; Claudio Lucio de Medeiros Albuquerque; Débora Paulo Santos; Demétrio Antonio Gonçalves da S. Gomes; Édson Cunha de Araújo Junior; Elizabete das Chagas Vilanova; et al. (Cadernos de Saúde Pública)
Abstract: This study aimed to describe the severity of abortion-related complications, factors associated with complications, the types of management and the experience of care in Brazil. A cross-sectional study in twenty hospitals (10 in Federal District, 3 in Rondônia and 7 in Maranhão). For 3 months, all women treated for abortion/miscarriage had their data collected. The severity of complications was defined according to World Health Organization criteria. Women with hemorrhage, infection or organs injury were invited to answer an interview about experience of care. Statistical analysis was performed using chi-square test and Poisson regression models. Among 1,683 women included, 82.5% had mild complications, 13.6% had moderate complications, 3.2% had potentially life-threatening conditions (PLTC) and 0.7% had severe maternal outcomes (SMO). Most women (94.2%) required uterine evacuation. Among these, 91.5% required surgical evacuation (with or without the use of uterotonics) and 8.5% used only uterotonics. The most frequent surgical evacuation method was curettage (66.9%), followed by manual vacuum aspiration (MVA) (32.3%). Factors associated with PLTC/SMO vs mild complications were having a gestational age ≥ 13 weeks (pravlence ratio - PR = 3.09; 95% confidence interval - 95%CI: 1.42-6.72), having been treated in Maranhão (PR = 0.27; 95%CI: 0.12-0.63) and in Rondônia (PR = 0.64; 95%CI: 0.20-0.99). Factors associated with moderate vs. mild complications were expulsion of products of conception before arrival to health facility (PR = 2.55; 95%CI: 1.64-3.96) and having been treated in Maranhão (PR = 0.58; 95%CI: 0.38-0.87). Most women who responded to the interview were treated kindly (95.6%), however, 66.7% felt stressed and 10.1% reported that their preferences were not respected during hospitalization. Nine out of ten women treated in Brazilian public hospitals due to abortion-related complications undergo some surgical procedure, the most common of which is uterine curettage. Approximately four in every hundred women experience severe complications. It is essential to ensure the supply of equipment for MVA and to encourage continuing medical education programs to increase the awareness of healthcare professionals about safer treatments for uterine evacuation.